Transforming Education in the 5.0 Era: Utilizing Technology to Improve Critical Thinking and Creativity in The Digital Generation - Oria Lasmana; Festiyet Festiyet; Abdul Razak; Muhyiatul Fadilah (Green Publisher, 2024)
The Era 5.0 is marked by a significant shift towards a more human-centered society supported by technology. This transformation is occurring in various fields, including education. Education in Era 5.0 must adapt and innovate to prepare digital generation graduates who are not only proficient in digital literacy but also possess high critical and creative thinking skills. This study aims to analyze the transformation of education in Era 5.0 by utilizing technology to enhance critical and creative thinking skills in the digital generation. The research applied the Systematic Literature Review (SLR) method. Information was obtained from reputable scientific journals and filtered through searches in electronic databases such as Google Scholar and Scopus. The data were then analyzed through three steps: data reduction, data presentation, and data analysis, followed by drawing conclusions. The study's findings indicate that the utilization of technology in education can improve students' critical and creative thinking skills. Technology can enhance these abilities by helping students reflect on presented data and question its veracity and reliability. Additionally, technology can encourage students to participate in group discussions, which helps them hone their critical and creative thinking skills in developing innovative solutions or arguments. Lastly, technology can provide students with more complex and challenging tasks that require higher-order thinking. Therefore, optimal use of technology is essential in education to address the challenges of the Education 5.0 era dominated by the digital generation.